Effects of drying and age plants on the composition of the essential oils of Lippia alba (Mill.) N.E.Br. ex Britton & P. Wilson and Lippia origanoides Kunth accessions - Johannes Delgado Ospina; Manuel Salvador Sánchez Orozco; Carmen Rosa Bonilla Correa (Acta Agronómica)
A test was conducted under field conditions at the Universidad Nacional de Colombia sede Palmira and oils analysis in the Universidad Industrial de Santander (UIS), in order to determine the effect of plant age at the time cutting and the effect of drying the plant material on the composition and concentration of the essential oils of three accessions of Lippia origanoides Kunth. (Patía, Cítrica and Típica) and two accessions of Lippia alba (Mill.) N.E.Br. ex Britton & P. Wilson (Cítrica and Típica). In a split plot arrangement with three replications, two factors were evaluated drying and three harvest times. The results showed that drying increased the concentration of the main components of the accessions of the two Lippia species, and age of the plants at harvest did not affect the composition and concentration of essential oils.